Pengaruh Problem-Based Learning (PBL) Terhadap Keterampilan Berpikir Kritis Siswa SMA pada Materi Perubahan Lingkungan - Candra Hermawan (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study was to determine the effect of a problem-based learning model (PBL) on the critical thinking skills about changes in the environment. This study adopted a quasi-experimental model with a non-equivalent group design. The subjects of this study are 10th students at SMA Negeri 1 Genteng for the 2020/2021 school year. The sampling technique used purposive sampling and chose 30 students in each of the experimental and control classes. Critical thinking skills data collection using 20 multiple choice questions tested for validity and reliability. Data analysis using independent sample t-test. The results show that there is a significant effect of the problem-based learning (PBL) model on students' critical thinking skills (p=0.000). Problem-based learning (PBL) has a greater influence on critical thinking skills than conventional learning. The use of problem-based learning (PBL) models on the topic of environmental change encourages students' critical thinking skills to be able to solve problems related to environmental change.Keywords: problem-based learning, critical thinking skills, environmental change